Subband transforms for adaptive direct sequence spread spectrum receivers - Berner, S.; De Leon, P. (Conference Record of Thirty-Fifth Asilomar Conference on Signals, Systems and Computers (Cat.No.01CH37256), 2001)
Adaptive DSSS receivers have advantages over their fixed-matched filter counterparts including interference cancellation capabilities and simplification of PN code acquisition. However, convergence using an LMS algorithm may be too slow in situations with relatively high SNR. The use of an RLS algorithm will improve the convergence speed but at significantly increased computational cost; fast RLS algorithms cannot be used because the filter is updated at the symbol rate rather than at every sample. We examine subband receivers which utilize multiple, shorter length adaptive filters with the goal of speeding up convergence and reducing computation while maintaining equivalent BERs.